ASUHAN KEPERAWATAN PADA PASIEN MEDIS EFUSI PLEURA DENGAN GANGGUAN PEMENUHAN KEBUTUHAN OKSIGENASI PADA NN.I DI RUANG SOEPARJO ROESTAM RSUD.PROF.DR.MARGONO SOEKARJO PURWOKERTO - Intan Mustadiroh; Ikit Netra W (Jurnal Inovasi Penelitian, 2023)
Background: Pleural effusion is the collection of fluid in the pleural space located between the visceral and parietal surfaces which will cause the accumulation of secretions and coughing. Effective coughing is a treatment activity to clear the airway that functions to increase the mobilization of secretions so as to facilitate the release of sputum. Objective: This case study discusses the implementation of effective cough in pleural effusion patients with nursing diagnosis of ineffective airway clearance. Method: Case study conducted on 1 patient by applying effective cough for 3 days from December 12 to 15, 2022. Results: After 3 days of nursing action, the nursing diagnosis of airway clearance is ineffective associated with restrained secretions resolved characterized by the patient being able to remove phlegm and no additional breathing sounds. Conclusion: Effective coughing affects sputum discharge in pelural effusion patients with airway clearance problems is not effective